Navigating data science in the age of AI : exploring possibilities of generative intelligence - Singla, Babita; Shalender, Kumar; Singh, Nripendra (Advances in digital technology and data-driven business practices, 2025)
The rapid rise of generative intelligence is apparent from its adoption prospects across industrial sectors. Business leaders are prioritizing applications of Generative Intelligence although the challenges related to this technology adoption also need to be addressed in detail. Navigating Data Science in the Age of AI: Exploring Possibilities of Generative Intelligence can offer significant contributions in the field of generative intelligence in the context of data science and help stakeholders formulate strategies to tackle its adoption, implementation, and control challenges. This volume takes a comprehensive view of the application of AI in the area of data science and how technology is transforming businesses in a range of industries. From FinTech to the use of chatbots to decision making to banking, the potentials as well as challenges are wide and far-reaching. The research presents a diverse range of authors from around the globe, bringing their unique perspectives and expertise to the conversation. Advances in Digital Technology and Data-Driven Business Practices examines the possibilities, challenges and ethics of a range of technologies applied in business, including: Metaverse, Marketing Automation, Search Engine Optimization (SEO), Search Engine Marketing (SEM), Social Media Marketing, Content Marketing, Analytics and Data Analysis, Augmented Reality (AR) and Virtual Reality (VR), Chatbots and Artificial Intelligence (AI). Adopting and adapting to these technologies is essential for staying competitive and effectively reaching target audiences.